TAX AND COMMUNITY EMPOWERMENT: THE IMPACT OF TAX CUTS PROGRAMMES FOR VULNERABLE GROUPS - Erwin; Loso Judijanto; Melyana R Pugu; Al-Amin; Hadenan Towpek (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Taxes and community empowerment are closely related in the context of tax cut programmes aimed at vulnerable groups. A tax cut is a reduction in tax burden granted by the government to certain individuals or groups to increase their disposable income. In vulnerable groups, which usually include low-income individuals, the elderly, and those in difficult economic conditions, tax cuts aim to reduce financial hardship and improve access to basic needs such as food, health, and education. The method used in this research uses the literature research method. The results show that the tax cut programme can significantly contribute to improving the welfare of vulnerable groups by increasing disposable income and reducing economic burden. However, the effectiveness of this programme is highly dependent on proper policy design, efficient implementation, and the government's ability to maintain fiscal balance. Focused and well-structured programmes tend to achieve better results in terms of community empowerment compared to generic or overly broad programmes. In addition, community involvement and transparency in programme implementation are also key factors in ensuring success and accountability. The study concludes that with proper planning and execution, tax deduction programmes can be an effective tool in empowering vulnerable groups and improving socio-economic welfare more broadly.